Plant growth and development - Leopold, A. Carl (McGraw-Hill, 1964)
Book has tree directions of special emphasis. First, to develop the student's reliance on ex periments in forming generalizations abouthis science; Second , to depict science as a complex of imperfect approximations derived by the scientific method; And third, to make it more nearly representative of modern plant physiology in the laboratory and in the field